Whole exome sequencing enables the correct diagnosis of Frank–Ter Haar syndrome in a Saudi family - Y. N. Khan; M. Imad A.M. Mahmud; N. Othman; H. M. Radzuan; S. Basit (Вавиловский журнал генетики и селекции)
Frank–Ter Haar syndrome (FTHS) is a rare genetic hereditary autosomal recessive disorder characterized by defective malformation of cardiovascular, craniofacial, and skeletal system. Mutations in the SH3PXD2B gene are a common cause in the development of FTHS. We recruited a family with two affected individuals (3-year-old female and 2-month-old male infant) having bilateral clubfoot. Family pedigree shows an autosomal recessive mode of inheritance. DNA was extracted from the blood samples of six members of the family. Whole exome sequencing was done for the two affected individuals and the variant was validated in the whole family by using Sanger sequencing approach. Whole exome sequencing (WES) data analysis identified a rare homozygous variant (c.280C>G; p.R94G) in the SH3PXD2B gene, and Sanger sequencing showed that the same variant perfectly segregates with the phenotype in the pedigree. Moreover, the variant is predicted to be damaging and deleterious by several computation tools. Revisiting the family members for detailed clinical analysis, we diagnosed the patients as having the typical phenotype of FTHS. This study enabled us to correctly diagnose the cases of FTHS in a family initially recruited for having bilateral clubfoot by using WES. Moreover, this study identified a novel homozygous missense variant (c.280C>G; p.R94G) in (NM_001308175.2) the SH3PXD2B gene as a causative variant for autosomal recessive FTHS. This finding supports the evidence that homozygous mutations in the SH3PXD2B gene are the main cause in the development of FTHS.